2023
DOI: 10.3390/jcm12051849
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Myocarditis and Cardiogenic Shock Following COVID-19 Infection Versus COVID-19 Vaccination: A Systematic Literature Review

Abstract: Background: Myocarditis, diagnosed by symptoms and troponin elevation, has been well-described with COVID-19 infection, as well as shortly after COVID-19 vaccination. The literature has characterized the outcomes of myocarditis following COVID-19 infection and vaccination, but clinicopathologic, hemodynamic, and pathologic features following fulminant myocarditis have not been well-characterized. We aimed to compare clinical and pathological features of fulminant myocarditis requiring hemodynamic support with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…This is particularly relevant considering that a recent meta-analysis compared fulminant myocarditis associated with COVID-19 infection versus COVID-19 vaccination. While this study reported a similarly high mortality rate and no differences in most biopsies/autopsies between these conditions, COVID-19 fulminant myocarditis was associated with a more aggressive course with more severe hemodynamic decompensation and more cardiac arrests [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant considering that a recent meta-analysis compared fulminant myocarditis associated with COVID-19 infection versus COVID-19 vaccination. While this study reported a similarly high mortality rate and no differences in most biopsies/autopsies between these conditions, COVID-19 fulminant myocarditis was associated with a more aggressive course with more severe hemodynamic decompensation and more cardiac arrests [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both males and females were almost equally distributed, and the median age was reported to be 45 years. The authors describe a comparably high necessity of inotropes and MCS paired with a high mortality rate of 27.7% [ 33 ]. Treatment options for myocarditis vary depending on the severity of disease and the underlying cause of myocarditis.…”
Section: Epidemiology Of Myocarditismentioning
confidence: 99%
“…Unlike other forms of FM that are primarily defined by their histological features, COVID-19-associated AM displays heterogeneous histological presentations [ 32 ]. In both COVID-19- and vaccination-associated forms, LM appears to be the most commonly reported pattern, followed by eosinophilic and mixed infiltrates [ 33 ]. Ammirati et al reported 10 fulminant cases that required temporary MCS systems with a median support time of 5 days.…”
Section: Epidemiology Of Myocarditismentioning
confidence: 99%
See 2 more Smart Citations